Bed Side Teaching and Case Study on Knowledge and Skill about Triage among Nursing Studentsin Emergency Unit: A Comparative Study - Ni Putu Kamaryati; Yustina Ni Putu Yusniawati; Ida Ayu Ningrat Pangruating Diyu (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2024)
Introduction: Clinical learning experiences in the emergency unit is needed to improve the knowledge and skill of nursing students. Bedside teaching and case study were suitable methods, however, there were inconsistent findings from previous studies. The study aimed to compare the effectiveness of the bed site teaching and case study on the knowledge and skills of nursing students in the emergency unit.Method: This study was a quasi-experimental design with two groups pretest and a posttest involving 80 respondents with 40 respondents in each group based on inclusion criteria in emergency units. The respondents were random sampling assigned into groups and received bedside teaching and case study methods per group. The knowledge about triage and clinical performances checklist were used as instruments. Data were analyzed using a descriptive statistic, Mann Whitney Test, and the Wilcoxon rank test by SPSS. Results: The findings found that there was a statistically significant difference in knowledge about triage and skill from baseline to Week 4 in the BST group and the Case study group (p< .001 and p< .001, respectively). Additionally, the study found a statistically significant difference in knowledge about triage and skill between groups at Week 4 (p< .001 and p< .001, respectively).Conclusion: The finding can utilize as one of the best learning methods in nursing practice to enhance student's knowledge and clinical performances in the hospital. It is needed to study in different units in a clinical setting for future study.